Public Private Cooperative Partnerships for Scaling Commercial Maize Production In Nepal: Linking Innovations With Policy - Choudhary, Dyutiman; Khanal, Narayan Prasad; Pandit, Naba Raj; KC, Dilli; Timsina, Krishna Prasad (Nepal Public Policy Review, 2023)
The Agriculture Development Strategy of the Government of Nepal (2015-2035) has identified maize as one of the key commodities for commercialization. Maize constitutes at least 50% of the total ingredients in poultry feed, with approximately 3,000 tons of poultry feed consumed daily in Nepal. However, while the demand for feed is increasing at about 10.0% per annum, maize production is only growing at 2.5% per annum. The low productivity with inferior grain quality and a lack of value chain coordination mechanisms starting from inputs (seeds) to output (grains) have hindered the commercialization of the domestic maize sector. Because of the inefficient market mechanism and competitive market structure, farmers are not able to pursue commercial maize production. To address this issue, action research on the value chain was conducted by the International Maize and Wheat Improvement Centre (CIMMYT), focusing mainly on Sudurpaschim and Lumbini provinces, to implement the maize commercialization model (MCM) between 2020 and 2022. Results demonstrate that public-private partnership approach can increase maize production, improve farm gate prices and farmers’ incomes, improve value chain coordination; improve access to services to farmers and enhance information flow among stakeholders. The study recommends that policies aimed to streamline commercial maize production should adopt a value chain approach, with a focus on chain upgrading and governance and promote coordination among actors to scale up commercial maize production throughout the maize-growing areas of Nepal.